2018
DOI: 10.1016/j.jim.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Using sweat to measure cytokines in older adults compared to younger adults: A pilot study

Abstract: Background/Objectives Current measures of cytokines involve urine, blood or saliva which have drawbacks including circadian rhythm variations and complicated collection methods. Sweat has been used to measure cytokines in young and middle-aged adults, but not older adults. We sought to determine the feasibility of using sweat to measure cytokines in older adults compared to younger adults. Design Two visit cross-sectional pilot study stratified by age group. Setting Independent living facility and Johns Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…This study involved active, passive, and thermal stimulation and all samples expressed at least one form of interleukin (IL)-1α or IL-1β. Other investigators have found similar results regarding IL-1 and have also detected IL-6, IL-8, IL-10, IL-31, tumor necrosis factor (TNF)-α, and transforming growth factor (TGF)-β in sweat (Cizza et al 2008;Dai et al 2013;Hladek et al 2018;Jones et al 1995;Marques-Deak et al 2006;Sato and Sato 1994) although IL-6 and TNF-α are not consistently detected (Dai et al 2013;Faulkner et al 2014).…”
Section: Cytokinesmentioning
confidence: 63%
“…This study involved active, passive, and thermal stimulation and all samples expressed at least one form of interleukin (IL)-1α or IL-1β. Other investigators have found similar results regarding IL-1 and have also detected IL-6, IL-8, IL-10, IL-31, tumor necrosis factor (TNF)-α, and transforming growth factor (TGF)-β in sweat (Cizza et al 2008;Dai et al 2013;Hladek et al 2018;Jones et al 1995;Marques-Deak et al 2006;Sato and Sato 1994) although IL-6 and TNF-α are not consistently detected (Dai et al 2013;Faulkner et al 2014).…”
Section: Cytokinesmentioning
confidence: 63%
“…It is projecting that by the year 2020, 50 billion individuals globally will own connected smartphones and will own over six connected devices. 10 Smartwatches, rings, body scales, and vests have the capability of producing rich volumes of longitudinal information on physiological proxies of the autonomic nervous system stress response, such as resting heart rate, heart rate variability, body temperature, electrodermal activity, and relative blood pressure, 1113 while body patches that measure cortisol 14 and inflammatory cytokines 15 and eye-tracking glasses and wireless EEG caps are getting closer to measuring additional objectives measures of stress in real-world settings. 16 Information from smartphone apps and sensors, both passive (phone use, social communication patterns, sleep, and location) and active (cognitive tasks) could reflect digital proxies of objective measures of stress.…”
Section: The Potential Power Of Integrated Digital Toolsmentioning
confidence: 99%
“…As a medium connected to the skin barrier, sweat is irreplaceable in immune function, skin moisture, temperature regulation and biological defense [9,10]. Not only antibody isotypes such as immunoglobulin (lg)A, lgE and lgG, but also cytokines including tumor necrosis factor (TNF)‐α, transforming growth factor (TGF)‐β and other interleukins have been found in sweat [11]. As a widely accepted biomarker, sweat chloride measurement is of great value in diagnosing and treating cystic fibrosis (CF) [12,13].…”
Section: Introductionmentioning
confidence: 99%